Operator representation of Gevrey ultradistributions algebra with supports on positive n-dimensional angle - Solomko, A.V. (Carpathian Mathematical Publications, 2009)
The representation of convolution Gevrey algebra of ultradistributions as commutant of the n-parametric strongly continuous semigroup of shifts in algebra of linear and continuous mappings over the space of ultradifferentiable Gevrey functions with supports on positive n-dimensional angle is proved.